ChemInform Abstract: Synthesis, Structure, and Chemical Bonding in CaCoSi. Issue 3 (January 2015) - Hoffmann, Andrea V.; Hlukhyy, Viktor; Faessler, Thomas F.
Abstract The intermetallic title compound is prepared by solid state reaction of the elements (Nb ampule, flowing Ar, 1223 K, 45 min) and characterized by powder and single crystal XRD, magnetic measurements, and TB‐LMTO‐ASA electronic structure calculations.